New voices in education: breaking the mold - Hussien, Suhailah (s.n, 2012)
This purpose of this book is twofold: first to introduce to the larger public the contribution to knowledge that the graduates have made and second, by drawing attention to the work of students to make a case for the quality of work the faculty members of the Institute of Education have been and are engaged in. The book compiles the students work in Islamization of education